2012
DOI: 10.1289/ehp.1104315
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Polycyclic Aromatic Hydrocarbon (PAH) Exposure and Child Behavior at Age 6–7 Years

Abstract: Background: Airborne polycyclic aromatic hydrocarbons (PAH) are widespread urban air pollutants from fossil fuel burning and other combustion sources. We previously reported that a broad spectrum of combustion-related DNA adducts in cord blood was associated with attention problems at 6–7 years of age in the Columbia Center for Children’s Environmental Health (CCCEH) longitudinal cohort study.Objectives: We evaluated the relationship between behavioral problems and two different measures of prenatal exposure—b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
188
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(203 citation statements)
references
References 50 publications
10
188
2
3
Order By: Relevance
“…Investigations on humans have shown the connection between urine, feces, or blood concentrations of BPA (total/free) and a diversity of health measures including mutation in fetuses, miscarriage, obesity and fertility in women, efect on the uterus lining ("endometrium"), certain hormones that support the control of deoxyribonucleic acid (DNA) damage to reproduction markers, length of gestation, polycystic ovary syndrome, and birth outcomes [42]. Only a small number of studies have summarized the relations between BPA exposure and disorders of reproduction or developmental efects in humans.…”
Section: Bpa Toxicity In Adultsmentioning
confidence: 99%
“…Investigations on humans have shown the connection between urine, feces, or blood concentrations of BPA (total/free) and a diversity of health measures including mutation in fetuses, miscarriage, obesity and fertility in women, efect on the uterus lining ("endometrium"), certain hormones that support the control of deoxyribonucleic acid (DNA) damage to reproduction markers, length of gestation, polycystic ovary syndrome, and birth outcomes [42]. Only a small number of studies have summarized the relations between BPA exposure and disorders of reproduction or developmental efects in humans.…”
Section: Bpa Toxicity In Adultsmentioning
confidence: 99%
“…BPA has also been found to induce apoptosis International Letters of Natural Sciences Vol. 27and cell arrest in cultured ovarian granulosa cells, suggesting that BPA may also impact the adult ovary. Many of the physiological effects of BPA have been described in the context of its ability to interact with classic ER (nuclear hormone receptor activity).…”
Section: F ) Effect On Reproductive Systemmentioning
confidence: 99%
“…27been questioned. Kinetics also varies markedly with route of administration, dose, age and even gender.…”
Section: F ) Effect On Reproductive Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26] Our previous research in a New York City birth cohort and in the present Krakow birth cohort revealed that prenatal exposure to PAH was associated with adverse cognitive outcomes at age 5 years 27,28 and with behavioral problems, including anxiety and depression, at ages 6 to 7 years in New York City. 29 Although there is some previous human evidence of interactions between socioeconomic factors and pollutants, [30][31][32][33][34] this is the first study assessing the interaction of PAHs and maternal psychological distress on neurobehavioral outcomes. [30][31][32][33] …”
mentioning
confidence: 91%